Military Environmental Literacy in the South African Army - Smit, H A P; Van Der Merwe, J H (Scientia Militaria - South African Journal of Military Studies, 2018)
Traditional military activities, such as fighting wars, are inherently destructive. Modern militaries undertake a diverse range of military activities, use large areas for military training and operational purposes, and are confronted with a global focus on environmentally responsible behaviour. These conditions compel militaries to ensure that soldiers display the correct attitude toward, behaviour in and knowledge about the diverse physical, social and cultural environments they occupy and on which they have an effect. Globally, and in South Africa, this is not only a moral obligation but a legal imperative too. The aim of this article is to report on the military environmental literacy (MEL) (attitude, behaviour and knowledge regarding the environment in which the military operate) of the members of the South African Army (SA Army). To achieve this aim, existing environmental questionnaires were evaluated to ascertain their suitability for use in an SA Army context. None of them was usable to appraise MEL in a SA Army context effectively. Consequently, an iterative process was initiated to develop a tailor-made, valid, reliable and organisation-specific questionnaire to assess MEL in the SA Army.